Health effects of children's summer holiday programs: a systematic review and meta-analysis - Emily Eglitis; Ben Singh; Timothy Olds; Rosa Virgara; Amanda Machell; Mandy Richardson; Kylie Brannelly; Aniella Grant; Jessica Gray; Terri Wilkinson; Zoe Rix; Grant R. Tomkinson; et al. (BMC, 2024)
Abstract Background Unfavourable changes occur in children's health behaviours and outcomes during the summer holidays. This systematic review aimed to determine the effectiveness of summer holiday programs in mitigating these changes. Methods Six databases (MEDLINE, JBI, PsychINFO, Embase, ERIC and Scopus) were systematically searched for experimental controlled studies that investigated programs of at least 5 days' duration conducted exclusively during the summer holiday period on school-aged children (5-18 years). Primary outcomes were moderate-vigorous physical activity and energy intake. Secondary outcomes were sedentary behavior, diet quality, adiposity, and cardiorespiratory fitness. Risk of Bias was assessed using the PEDro tool. Effect sizes were calculated using random-effects meta-analysis with narrative synthesis of effects by student or program characteristics. Results Ten studies (two randomised controlled trials, and eight non-randomised controlled trials) involving 1,446 participants were included. Summer programs had a significant moderate effect on reducing sedentary behaviour (g= -0.59, 95%CI= -1.16, -0.03) and significant small effects on improving moderate-to-vigorous physical activity (g = 0.35, 95%CI = 0.02, 0.67) and adiposity (g= -0.25, 95% CI = -0.39, -0.10). No significant change was detected for cardiorespiratory fitness (g = 0.43, 95%CI= -0.32, 1.17), energy intake (g= -0.06, 95% CI -2.33, 2.22), or diet quality (g = 0.20, 95%CI= -0.43, 0.83). Summer program effectiveness did not appear to differ by child sociodemographic or program characteristics. Concerns regarding bias and high heterogeneity impacted results. Conclusions Summer programs show potential in promoting healthier movement behaviours in children and supporting healthy body weight during the summer months. Although evidence from the included studies has limitations, these programs produced small to moderate effect sizes and present promising health intervention opportunities for children. Future research with more rigorous study designs and comprehensive reporting is needed to confirm these findings and better understand the impact of summer programs on children's health. Prospero registration CRD42023409795.